Knowledge, attitude, and practice of physicians towards familial hypercholesterolemia in north regions of Saudi Arabia - Alsaidan, Aseel Awad (Journal of the Pakistan Medical Association, 2024)
Objectives: To assess knowledge, attitude and practice of physicians regarding familial hypercholesterolemia. Method: The cross-sectional study was conducted from October to December 2022 in Aljouf, Tabouk, Hail and northern border regions of Saudi Arabia after approval from the ethics review committee of Qurayyat Health Affairs. Those included were physicians specialising in familial hypercholesteremia and having experience in family medicine, endocrinology, paediatrics, cardiology, internal medicine and obstetrics and gynaecology. Their knowledge, attitude and practice were assessed using a predesigned questionnaire. Data were analysed using SPSS 20. Results: Of the 430 subjects, 220(51.2%) were males, 89(20.7%) were aged 36-40 years, 169(39.3%) were residents, and 146(34%) had experience >15 years. Overall, 270(62.8%), 286(66.5%) and 287(66.7%) subjects did not know about the clinical diagnostic algorithms of Simon Broom, Dutch Lipid Clinic Network and United States MedPed programme investigated criteria, respectively. There were, 149(34.7%) subjects with high awareness level, and the level of awareness was significantly affected by gender, level of training, medical specialty, and familiarity with familial hypercholesteremia (p<0.05). There were 343(79.8%) subjects who said they had never diagnosed familial hypercholesteremia. Conclusion: There were knowledge gaps, low awareness, and inappropriate practices related to familial hypercholesterolemia, indicating the need for targeted programmes. Key Words: Familial hypercholesterolemia, Cholesterol, Genetic, Cardiovascular disease.